2020
DOI: 10.3390/jof6040259
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Multilocus Sequence Typing Scheme for Pneumocystis jirovecii

Abstract: Pneumocystis jirovecii is an opportunistic human pathogenic fungus causing severe pneumonia mainly in immunocompromised hosts. Multilocus sequence typing (MLST) remains the gold standard for genotyping of this unculturable fungus. However, the lack of a consensus scheme impedes a global comparison, large scale population studies and the development of a global MLST database. To overcome this problem this study compared all genetic regions (19 loci) currently used in 31 different published Pneumocystis MLST sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…The primers used in this study are listed in Table I . The PCR amplification conditions for β-Tub and 26S were the same as those previously reported ( Pasic et al 2020 ), and the conditions for other genes were the same as described in previous studies ( Lee et al 1998 ; Wang et al 2019 ; Xue et al 2019 ). DNA from P. jirovecii -positive specimens stored in our laboratory was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primers used in this study are listed in Table I . The PCR amplification conditions for β-Tub and 26S were the same as those previously reported ( Pasic et al 2020 ), and the conditions for other genes were the same as described in previous studies ( Lee et al 1998 ; Wang et al 2019 ; Xue et al 2019 ). DNA from P. jirovecii -positive specimens stored in our laboratory was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“… ITS – internal transcribed spacer regions of rRNA operon, sod – superoxide dismutase, dhfr – dihydrofolate reductase, dhp – dihydropteroate synthase, WT – wild-type, cyb – cytochrome b, mt – mitochondrial large rRNA subunit, β-Tub – β-tubulin, 26S rRNA – 26S ribosomal RNA gene a – the genotype nomenclature based on previously published studies and b – the genotype locations according to the studies previously reported ( Walker et al 1998 ; Ma et al 1999 ; Beard et al 2000 ; Denis et al 2000 ; Takahashi et al 2002 ; Esteves et al 2010b ; Maitte et al 2013 ; Xue et al 2019 ; Pasic et al 2020 ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unculturable fungi present a challenge, and more targeted methods are needed. For instance, a successful consensus multilocus sequence typing scheme for P. jirovecii 75 enables antifungal resistance marker analysis 76 . For Aspergillus spp., more knowledge of resistance mechanisms is required as many resistant isolates do not carry the few known resistance-associated alleles 77 .…”
Section: Diagnostics and Surveillancementioning
confidence: 99%
“…The evolution of molecular tools for the detection of fungal pathogens has been slow in the last decades, but has significantly advanced in recent years. Several of the reviews and articles deal with the diagnostic repertoire of the mycology laboratory and show the value of new and well-established tests [ 12 , 13 ].…”
mentioning
confidence: 99%